FTIR study of the interaction of crotyl alcohol and crotonic acid with surface of SiO2, TiO2 and ZrO2 - Lochař, Václav; Pytel, Martin; Smoláková, Lucie (University of Pardubice, 2009)
Infrared studies of crotyl alcohol (2-butene-1-ol) and crotonic acid (2-butenoic acid) adsorption were carried out on SiO2, TiO2 and ZrO2 supports. The results were used to analyze the surface intermediates of crotonaldehyde dehydrogenation to maleic anhydride. Crotyl alcohol was adsorbed mainly in the alkoxide form at room temperature on all the studied oxides. Crotonaldehyde and consequently also carboxylate were products of reaction between the crotyl alcohol and active sites of ZrO2 surface at higher temperatures. During crotonic acid adsorption the undissociated acid molecules and the formation of hydrogen-bonded acid with surface hydroxyls were indicated for all the studied oxides. Crotonic acid was easily dissociated to form the surface carboxylate species on ZrO2. The presence of two different symmetric carboxylate species (maleate and crotonate) was shown from IR spectra following the crotonic acid adsorption.